Nanohybrids of oxides nanoparticles-chitosan and their antimicrobial properties. (22nd October 2022) - Matyjasik, Wiktoria; Długosz, Olga; Lis, Kinga; Banach, Marcin
Abstract: Growing international problem with pathogens acquiring resistance to antibiotics is the reason for the search for bactericidal substances against which microorganisms cannot become resistant. The aim of this study was to synthesize inorganic–organic nanohybrids and obtain materials with antimicrobial effects. Chitosan (CS) was deposited on nanocomposite carriers such as calcium oxide with titanium dioxide (CaO-TiO2 ), magnesium oxide with titanium dioxide (MgO-TiO2 ) and copper(II) oxide with titanium dioxide (CuO-TiO2 ). The efficiency of the process was examined at varying concentrations of chitosan and temperature. The parameters for nanohybrids synthesis were selected based on the highest amount of nano-chitosan deposited on the nanohybrids—for each carrier, the process conditions were as follows: chitosan solution at 5 g l −1 and 20 °C. The materials were obtained using these parameters and were used for microbiological tests against E. coli ATCC 25922, S. aureus ATCC 25923 and C. albicans ATCC 10231. The growth inhibitory activity of the obtained materials was qualitatively defined. These results suggest that the synthesized nanohybrids and nanocomposites exhibit biostatic action. The material with the broadest effect was the CuO-TiO2 -CS hybrid, which had biostatic properties against all tested strains at a minimal concentration of 1250 μ g ml −1 . Further research is required to find eco-friendly, non-toxic, and more effective antimicrobials with a broad action to prevent the acquisition of resistance.